Aeolian Remobilisation of the 2011-Cordón Caulle Tephra-Fallout Deposit: Example of an Important Process in the Life Cycle of Volcanic Ash - Dominguez, Lucia; Bonadonna, Costanza; Forte, Pablo; Jarvis, Paul Antony; Cioni, Raffaello; Mingari, Leonardo; Bran, Donaldo; Panebianco, Juan Esteban (Frontiers in Earth Science, 2020)
Although volcanic eruptions represent short periods in the whole history of a volcano, the large amount of loose pyroclastic material produced, combined with aeolian processes, can lead to continuous, long-lasting reworking of volcanic products. Driven by wind, these processes significantly influence the geomorphology and prolong the impacts of eruptions on exposed communities and ecosystems. Since such phenomena are of interest to scientists from a range of disciplines (e.g. volcanology, atmospheric and soil sciences), a well-defined, common nomenclature is necessary to optimize the multidisciplinary characterisation of both processes and deposits. We, therefore, first describe ash wind-remobilisation processes and provide definitions for appropriate terms consistent with the World Meteorological Organization’s classification of lithometeors. Secondly, we investigate the aeolian transport and deposition of ash from the 2011 Cordόn Caulle (Chile) tephra-fallout through field observations and on a physical characterisation of systematically collected ground and airborne material. In the arid regions of the Argentinian Patagonia steppe, two main types of secondary deposits have been identified associated with: i) non-erodible surface roughness elements (e.g. vegetation and rocks), and ii) pre-existing mounds or similar erodible bedforms. Grainsize analysis shows that wind-remobilised particles have a specific size range, from <0.4 to 500 m, with a 95% of the material between 1 and 255 m, median values of 25-135 m and modes of 30-95 m. We find that 15-40% of the remobilised material ranges from 63-125 m, coinciding with the size range which minimises the wind threshold friction velocity. Interestingly, particle shape analysis shows that for this size fraction, remobilised particles display the largest differences in shape descriptors (convexity, solidity and circularity) with respect to the primary ash, indicating abrasion and rounding due to saltation. Although particle (size and shape) and deposit features (morphology and structures) alone are insufficient to interpret transport mechanisms, their combination suggests that whilst saltation is the most common particle transport mechanism, suspension and creep also play an important role. In fact, our results suggest that saltation induces short-term suspension of fine particles (20-63 m).